Prototropic molecular-zwitterionic tautomerism of xanthine and hypoxanthine: unexpected biological view - Kondratyuk, I.V.; Samijlenko, S.P.; Kolomiets, I.M.; Potyahaylo, A.L.; Hovorun, D.M. (Биополимеры и клетка, 2000)
The prototropic molecular-zwitterionic tautomerism of xanthine and hypoxanthine has been investigated by the semi-empirical quantum-chemical AMI method. Geometric, energetic and other physico-chemical features of their complete molecular-zwitterionic families of tautomers have been established. The influence of the environment with universal solvatation mechanism on the tautomeric equilibrium has been evaluated at Otizager approximation. The comparison of the calculations with the ¹H NMR data favours the N7H Xan and the N9H Hyp tautomers in DMSO solutions. A possible biochemical role of tautomeric (especially zwitterionic) forms of Xan and Hyp is discussed. The stabilizing influences of both environment and specific interactions with proteins on rare tautomeric forms are considered. The biological significance of high energy tautomers is discussed. Напівемпіричним квантово механічним методом AMI досліджено прототропну таутомерію ксантину та гіпоксантину. Були встановлені геометричні, енергетичні та інші фізикохімічні характеристики їхніх повних молекулярно-цвітеріонних сімейств таутомерів. Вплив оточення з універсальним механізмом сольватації на таутомерну рівновагу оціненої в наближенні Онзагера. Зіставлення розрахунків з даними ¹Н ЯМР свідчить на користь таутомерів N7H та N9H для ксантину та гіпоксантину відповідно в ДМСО. Обговорюється можлива біологічна роль таутомерних форм (особливо цвітеріонних) ксантину та гіпоксантину. Розглянуто стабілізуючий вплив оточення та специфічні взаємодії з білками на рідкісні таутомерні форми. Обговорюється біологічне значення високоенергетичних таутомерів. Полуэмпирическим квантовомеханическим методом AMI исследована прототропная таутомерия ксантина и гипоксантина Были установлены геометрические, энергетические и другие физико-химические характеристики их полных молекулярно-цвиттерионных семейств таутомеров. Влияние окружения с универсальным механизмом сольватации на таутомерное равновесие оценено в приближении Онзагера- Сопоставление расчетов с данными ¹Н ЯМР свидетельствует в пользу таутомеров N7H и N9H для ксантина и гипоксантина соответственно в ДМСО. Обсуждается возможная биологическая роль таутомерных форм (особенно цвиттерионных) ксантина и гипоксантина. Рассмотрено стабилизирующее влияние окружения и специфические взаимодействия с белками на редкие таутомерные формы. Обсуждается биологическое значение высокоэнергетических таутомеров.